Positioning Daerah Tujuan Wisata Berdasarkan pada Kepuasan, Image dan Loyalitas Konsumen (Studi pada Daerah Tujuan Wisata Malang Raya) - Martaleni -; Djumilah Zain; Mintarti Rahayu; Djumahir - (Jurnal Aplikasi Manajemen, 2012)
This study aims to test the relationship between service quality, satisfaction, image and customer loyalty as the basis of evaluating and identifying niche market that can be used for the positioning strategy development or repositioning of tourism destination. Data were collected from domestic tourists coming from outside of Malang Raya. The tourists were asked using closed and open questions. Also, 232 questionnaires were collected and analyzed using statistical techniques Partial Least Square (PLS). The open questions were presented to explain to strengthen the uniqueness of tourist destination in Malang Raya as a whole.This study found that there was a strong influence of service quality on customer satisfaction and the two variables were positively affected customer image and loyalty. Based on the value of the relationship between the variables of service quality and customer satisfaction, it was obtained that the indicator of a tourist attraction was the most powerful indicator in measuring consumer satisfaction. The statistical test results and analysis of open questions identified that market niche for the development of tourist destination positioning Malang Raya were as recreational and natural tourisms.Keywords: Positioning, Quality Service, Customer Satisfaction, Image, Consumer Loyalty, Market Niche